Is the statutory retirement age contributing to youth unemployment?: The case of Portugal - Tostão, Ana Catarina Justino (2025)
Portugal is one of the most ageing countries in Europe. The pressure on public finance exerted by a higher share of older - and, consequently, retired - people is being filled, to some extent, with pub- lic policies aimed at increasing the statutory retirement age. At the same time, Portugal registers a systematically high youth unemployment rate. In a context of ageing population, is the minimum statutory retirement age playing a role on the unemployment of younger people, by keeping older people in the labour market for longer? Using 1992-2021 quarterly data and distinct econometric methods, estimates suggest the opposite: younger and older workers seem to act as complements in the labour market, rather than as substitutes. The results shed light on the relationship between both age groups in the labour market: increases in the employment of older people lead youth em- ployment to increase and youth unemployment to decrease. The latter relationship is only significant after 2013, with the end of the economic crisis and subsequent policies to fight unemployment. There is evidence of distinct patterns according to gender, region and educational attainment.